Clinicopathologic features and prognostic factors of tall cell variant of papillary thyroid carcinoma: comparison with classic variant of papillary thyroid carcinoma. Issue 10 (October 2015) - Okuyucu, Kursat; Alagoz, Engin; Arslan, Nuri; Emer, Ozdes; Ince, Semra; Deveci, Salih; Ayan, Asli; Taslipinar, Abdullah; Gunalp, Bengul; Azal, Omer
Abstract : Objective: Tall cell variant (TCV), an aggressive form of papillary thyroid carcinoma (PTC), frequently presents with extrathyroidal disease and recurrence. The aim of this study was to evaluate the clinicopathologic features and outcomes of patients with TCV by comparing them with a larger group of patients with classic variant of papillary thyroid carcinoma (cPTC). Patients and methods: A total of 2500 patients with differentiated thyroid carcinoma were treated and monitored during a 23-year period (1992–2015). Of them, 2250 (90%) had PTC and 235 (9.5%) had follicular thyroid carcinoma. Of the 2250 patients, 862 (38.3%) and 70 (3.1%) had cPTC and TCV, respectively. Cases of TCV and cPTC of PTC were compared on the basis of risk factors. Results: Patients with TCV were significantly older compared with cPTC patients ( P <0.001). Tumor size was significantly bigger ( P =0.01) and preablation thyroglobulin level was significantly higher ( P <0.001) in TCV patients than in cPTC patients. The incidence of capsule invasion, extrathyroidal extension, and vascular invasion was significantly higher in TCV ( P =0.003, <0.001, and 0.011, respectively). The incidence of initial lymph node metastasis was significantly higher in TCV ( P <0.001). Patients with TCV were mostly at an advanced stage compared with patients with cPTC ( P <0.001). Development of local or distant metastasis during the follow-up was significantly higher in TCV than in cPTC. Sex and multifocality were not statistically significant. Conclusion: TCV has a higher incidence of local or distant metastasis and mortality rate. Thus, it must be treated with the highest possible 131 I ablation doses and followed up carefully.